Greening of arid Australia: New insights from extreme years. (15th July 2013) - Wardle, Glenda M.; Pavey, Chris R.; Dickman, Chris R.
Abstract In comparison with drylands elsewhere, the unpredictability of rainfall in central Australia is globally distinctive. The transformative rhythms of arid Australia reflect extremes of climatic conditions rather than seasons, and are characterized by irregular pulses of productivity that punctuate long periods of drought. These decadal‐scale dynamics are only now beginning to be understood. Further complications in predicting and managing the biological processes within these landscapes arise from the vast spatial extent of arid and semi‐arid communities, and increasing recognition of the heterogeneities that drive the formation of patterns across multiple scales. In 2010 and 2011 flooding rains broke long‐standing rainfall records and triggered an anticipated greening of the typically dry red landscapes of central Australia. These unusual climatic events provided an unparalleled opportunity to test ideas about productivity and function, bottom‐up versus top‐down effects, and differential responses of biota that reflect landscape connections and heterogeneity. Migrations of species outside their known ranges, irruptions of rodents and redistribution of resources are just a few of the novel observations that were reported. The transformation of the landscape also presented land managers with challenges stemming from the influx of invasive species that trigger novel ecological interactions and processes. The papers presented in this special issue describe how ecologists and managers responded to the unprecedented rainfall events, key lessons that we have learnt, and practical recommendations on how to improve conservation outcomes for the fragile inland environment into the future.